2019
DOI: 10.1523/jneurosci.3120-18.2019
|View full text |Cite
|
Sign up to set email alerts
|

Disinhibition of the Nucleus Accumbens Leads to Macro-Scale Hyperactivity Consisting of Micro-Scale Behavioral Segments Encoded by Striatal Activity

Abstract: The striatum comprises of multiple functional territories involved with multilevel control of behavior. Disinhibition of different functional territories leads to territory-specific hyperkinetic and hyperbehavioral symptoms. The ventromedial striatum, including the nucleus accumbens (NAc) core, is typically associated with limbic input but was historically linked to high-level motor control. In this study, performed in female Long-Evans rats, we show that the NAc core directly controls motor behavior on multip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 69 publications
4
13
0
Order By: Relevance
“…The dissociation between LFP spikes and tic expression was first documented by Muramatsu et al, where striatal LFP spikes remained present after the cooling or lesioning of the cortex, whereas motor tics were not detectible in the EMG signal (Muramatsu et al, 1990;McCairn et al, 2016). A similar dissociation was also documented in our lab model of hyperactivity, in which striatal disinhibition was limited to the limbic region (Yael et al, 2019). In this case, the abnormal behavior involved overall increased locomotion, whereas the LFP spikes were partially correlated with movement stops.…”
Section: Discussion (1499/1500)supporting
confidence: 83%
“…The dissociation between LFP spikes and tic expression was first documented by Muramatsu et al, where striatal LFP spikes remained present after the cooling or lesioning of the cortex, whereas motor tics were not detectible in the EMG signal (Muramatsu et al, 1990;McCairn et al, 2016). A similar dissociation was also documented in our lab model of hyperactivity, in which striatal disinhibition was limited to the limbic region (Yael et al, 2019). In this case, the abnormal behavior involved overall increased locomotion, whereas the LFP spikes were partially correlated with movement stops.…”
Section: Discussion (1499/1500)supporting
confidence: 83%
“…Excitation of PVT can also disrupt behaviour under this conflict but because it suppresses selection of behaviour. This effect of PVT excitation would be the opposite, but complementary, to the non-selective increases in frequency of normal behavior (Yael et al, 2019) and neural activity (Millan et al, 2010) observed after non-selectively inhibiting Acb and is worth further investigation (e.g., Chisholm et al, 2019).…”
Section: Pvt and Conflict Between Motivational Systemsmentioning
confidence: 95%
“…In the current implementation of the model, the dorsomedial loop receives a desired goal signal (here, a desired outcome fruit) and an associated stimulus signal (observed box with fruit icon) as inputs (Figure 2A). Although the goal selection process is not explicitly modeled, we assume that it involves the limbic network (Groenewegen et al, 1997(Groenewegen et al, , 1999Corbit et al, 2001;Balleine et al, 2003;Gönner et al, 2017), including the ventral striatum (Yael et al, 2019). The dorsomedial loop uses reward signals to learn to select an intended button which is transferred to the dorsolateral loop as a reference signal.…”
Section: Modeling Frameworkmentioning
confidence: 99%